PERAN PERAWAT PUSKESMAS DALAM PENANGGULANGAN JENTIK AEDES AEGYPTI PADA TPA - Aji, Rustam (JURNAL MEDIA KESEHATAN, 2016)
The role of nurses in health worker empowerment, to combat theAedesAegypti mosquito density through organized community efforts throughenvironment.Peran sanitation sanitation workers is very important to optimize cadresjumantik to reduce morbidity, the incidence of dengue fever. The purpose of this studywas to determine the characteristics of the informer Age, Gender, Education andEmployment, retrieval and processing of data from July 24 until October 24, 2015,population and samples were taken to the informer officers in puskesmas perumnasinclude: Head of Unit, Coordinator of dengue hemorrhagic fever, Clinical instructor,eradication of communicable diseases, sanitation also involve self-employed. The place ofresearch in Puskesmas Batu Galing Village Housing, type of qualitative researchphenomenological approach, information was collected through in-depth interviews at 6informants. Test the validity of the triangulation of sources, methods and investigator,aims to describe the role of nurses in the health center health worker empowerment forprevention of Aedes aegypti larvae density on water reservoirs. Three informants (49.5%)with health education, four informants (66.0%), reported to the Health Department forfogging, four informants (66.0%), to provide counseling, use of abate, four informants(66.0% ), carry out the drain, closing and hoarding (3 M) + Plus, 1-week evaluationinformer informant 1 and 2 (33.0%), respectively 1 of 6 informants (16.5% with healtheducation, mutual cooperation , larva survey each quarter, draining water reservoirs,overseeing larvae in water reservoirs, once a week. Suggested for Preventing thedevelopment of mosquito larvae by draining water reservoirs, mutual assistance, andcounseling Aedes Aegypti mosquito eradication and prevention of dengue fever, the nursesanitation, health cadre active role in the dissemination of information and motivation tothe community.